Haizao Yuhu decoctions including three species of glycyrrhiza protected against propylthiouracil-induced goiter with hypothyroidism in rats via the AMPK/mTOR pathway. (5th October 2022) - Li, Na; Li, Muyun; Xiu, Linlin; Liao, Wenyong; Ren, Yuna; Liu, Haiyan; Chen, Shaohong; Chen, Feng; Yu, Xue; Fan, Angran; Huo, Min; He, Jia; et al.
Abstract: Ethnopharmacological relevance: Glycyrrhiza and sargassum are among the 18 incompatible medicaments according to traditional Chinese medicine (TCM) theory. Although it contains glycyrrhiza and sargassum, Haizao Yuhu decoction (HYD) is a classic prescription widely used as TCM to treat goiter. According to the Chinese Pharmacopoeia, glycyrrhiza is divided into three varieties: Glycyrrhiza uralensis Fish., Glycyrrhiza glabra L., and Glycyrrhiza inflata Bat. Whether the three varieties of glycyrrhiza have different efficacy or toxicity when applied in the HYD is unknown. Aim of the study: To explore whether the HYDs comprising three varieties of glycyrrhiza have different efficacy or toxicity when used to treat goiter in rats and the underlying mechanisms of these HYDs. Materials and methods: For two weeks, the goiter model was replicated by intragastric propylthiouracil (PTU) administration. Samples were divided into the control group, model group, euthyrox group, HYD with glycyrrhiza uralensis (HYD-U) group, HYD with glycyrrhiza glabra (HYD-G) group, and HYD with glycyrrhiza inflata (HYD-I) group. After four weeks of treatment, body weight, rectal temperature, thyroid/liver/kidney coefficient, thyroid/liver/kidney function, thyroid/liver/kidney histomorphology, and thyroid ultrastructure were evaluated. Then, real-time quantitative reverse-transcription polymerase chain reaction (RTqPCR), Western blot, and immunofluorescence analyses were performed to detect genes and proteins affecting autophagy and apoptosis in thyroid cells in the AMP-activated Protein Kinases (AMPK)/Mammalian target of rapamycin (mTOR) pathway. Results: All three HYDs increased thyroid hormones (THs) levels, relieved thyroid pathological tissue and ultrastructure, and activated vital proteins and genes in the AMPK/mTOR pathway. Comparisons among the efficacy of the three HYDs indicated that HYD-U restored the THs most effectively; however, no difference in the anti-goiter effect was observed. Moreover, the three HYDs resulted in no toxicity and promoted the recovery of impaired liver and kidney function caused by PTU. Comparisons among the recovery effects of the three HYDs on the liver and kidney were the same. Conclusion: Our experiments demonstrated that the three HYDs had outstanding anti-goiter effects and protected liver and kidney function. Their anti-goiter effects were attributed to AMPK/mTOR pathway-induced autophagy and apoptosis. HYD-U resulted in the best THs recovery. It was further indicated that in our present study, glycyrrhiza and sargassum were compatible in the three HYDs, thereby suggesting their safety of compounding in HYD and providing a basis for the research of the 18 incompatible medicaments. Graphical abstract: Image 1